The contribution of culture to the creation of inclusive and sustainable economies - Isabel Vieira; Andreia Silva; Elisa Alén; Didiana Fernandes (Millenium)
Introduction: Cultural and natural heritage is an irreplaceable repository of knowledge and a fundamental resource for sustainable development.